PENGARUH REWARDS INSTRUMENTALITIES DAN ENVIRONMENTAL RISK FACTORS TERHADAP MOTIVASI PARTNER AUDITOR INDEPENDEN UNTUK MELAKSANAKAN AUDIT PEMERINTAH - Mardiasmo, Mardiasmo (Journal of Indonesian Economy and Business, 2002)
There is an evidence that only a limited number of independent audit firms are interested in performing governmental audit (OâKeefe,1992). Furthermore, non-governmental auditors are believed to be less âindependentâ and proner to lose sight of programmatic demand to safeguard public trust than governmental auditors.To understand the supply of governmental audit services better, the gates independent audit firm partnerâs opinions on governmental audits and their motivation to pursue these engagements. The survey measures partnerâs belief about rewards instrumentalities derived from governmental audits and effects of the two risk factors, authority changes and political climate, on partner motivation to pursue governmental audits.The results of the multiple regression study between independent (rewards instruments and environmental risk factors) and dependent (partner motivation) show that rewards instrumentalities have a positive correlation towards partner motivation, whereas environmental risk have a negative one.It can be generally concluded that partners often act cautiously before accepting an enggagement letter offer to perform governmental audit, because of its environmental risk factors; in the form of authority changes and political climate. Though in practice, it will intensify rewards instrumentalities in the form of personal enjoyment, career opportunities and audit partner status.Keywords: partner motivation, intrinsic and extrinsic rewards, personal enjoyment, career opportunities, status, environmental risk factors, political climate, authoritative changes, decoupled.